Electronic correlations in twisted bilayer graphene near the magic angle - Choi, Youngjoon; Kemmer, Jeannette; Peng, Yang; Thomson, Alex; Arora, Harpreet; Polski, Robert; Zhang, Yiran; Ren, Hechen; Alicea, Jason; Refael, Gil; von Oppen, Felix; Watanabe, Kenji; et al. (Nature physics, 2019)
Twisted bilayer graphene with a twist angle of around 1.1° features a pair of isolated flat electronic bands and forms a platform for investigating strongly correlated electrons. Here, we use scanning tunnelling microscopy to probe the local properties of highly tunable twisted bilayer graphene devices and show that the flat bands deform when aligned with the Fermi level. When the bands are half-filled, we observe the development of gaps originating from correlated insulating states. Near charge neutrality, we find a previously unidentified correlated regime featuring an enhanced splitting of the flat bands. We describe this within a microscopic model that predicts a strong tendency towards nematic ordering. Our results provide insights into symmetry-breaking correlation effects and highlight the importance of electronic interactions for all filling fractions in twisted bilayer graphene. Scanning tunnelling microscopy shows that electrons in twisted bilayer graphene are strongly correlated for a wide range of density. In particular, a correlated regime appears near charge neutrality and theory suggests nematic ordering.